PERANAN BALING BALING PADA GERAKAN KAPAL - Utomo Budi (Diponegoro University, 2012)
Propellers is part movement propulsion system of the ships wich duty for pushing of the ship at forwardmovement and towing the body of ship at backward movement. As a part mechanical drive propeller consist ofsome blade attached to the boss and mounted on the propeller shaft of the axis relationships from the mainengine of the ships. Propeller can drive of the ships both forward and backward with by rotating on its axis. Toproduce forward and backward movement of the ships can be done in two ways namely with use controllablepitch propellers and with use fixed pitch propellers.